Effects of Thermal Neutron Irradiation on a Self-Refresh DRAM - Luza, Lucas Matana; Soderstrom, Daniel; Puchner, Helmut; Alia, Ruben Garcia; Letiche, Manon; Bosio, Alberto; Dilillo, Luigi (2020 15th Design & Technology of Integrated Systems in Nanoscale Era (DTIS), 2020)
In this study, static and dynamic test methods were used to define the response of a self-refresh DRAM under thermal neutron irradiation. The neutron-induced failures were investigated and characterized by event cross-sections, soft-error rate and bitmaps evaluations, leading to an identification of permanent and temporarily stuck cells, block errors, and single-bit upsets.